1-D shallow water equation, with no viscosity and no rotation, for a topography represented by a quadratic function. (7th August 2020) - Cortés-Vélez, Catalina; Martín-Atienza, Beatriz; Hernandez-Walls, Rafael
Abstract: Based on the linearized shallow water equations with no rotation and no viscosity, in a rectangular channel with topography, the analytical solution for elevation and velocity was obtained. The bathymetry of the rectangular channel is described by a quadratic function. The analytical solution was determined from generalized power series, resulting in numerically convergent power series. This methodology is a useful and easy tool, which can be used by teachers in the teaching of differential equations and modeling.